Self-pollination in the production of seed of Buffel grass (Cenchrus ciliaris L.). - Conde-Lozano, Elizabeth (2011)
The objective of this study wasto compare different forms of pollination on the characteristicsof seed of four varie tie s of Buffel grass. The study was carrie dout in the greenhouse and in the field of UAM Agronomiay Cie ncia s in the Municipa lity of Victoria , Tamaulipa s. Weused four varie tie s of Buffel grass (Comun, Nueces, T-1754and Formidable) which were subjected to two types ofpollination (free and self-pollination). The design used wasa completely randomized blocks design. Day at floweringof male and female organs was measured. In addition,pollen was classified (fertile, intermediate and infertile), andthe effects of self-pollination and free pollination free onthe characteristics of seed were recorded. No effects wereobserved on days at flowering of female organs (P = 0.54), butthe male organs were affected (P = 0.03), so that Formidablevarie ty plants required 2.3 days to mature. The number offertile, intermedia te and infertile pollen grains was not affectedby pollination or varie ty. All seed components were affected(P < 0.01) by the type of pollination, and the plants subjectedto self-pollinating showed the best features. Pollinationaffected the characteristics of the seeds.